Tools for 21st century diplomacy : an approach to improved information and communication technology for Romania's Foreign Affairs Ministry - Bikson, Tora K., 1940-; Anderson, Robert H. (Robert Helms), 1939-; Hunter, Robert Edwards, 1940-; Rand Corporation; United States. Trade and Development Agency (Santa Monica, CA : RAND, 2002)
At the request of Romania's Ministry of Foreign Affairs (MFA), the authors conducted a preliminary needs assessment and feasibility study of information and communication technology (ICT) in the Ministry to lay the foundation for future modernization stages, including the development of a detailed system design and subsequent system implementation. The researchers see future ICT implementation as having two main components: (1) providing a basic infrastructure for digital work practices and (2) completing projects to improve specific critical business processes. The MFA has made a go-ahead decision for ICT modernization, and the initial pieces of an implementation strategy are in place. The study suggests that the Ministry immediately acquire the needed human and financial resources to take the next implementation steps. Current positive developments in the Romanian government indicate that now is the right time for the MFA to move forward aggressively on its modernization agenda.
"May 2002."
Includes bibliographical references (p. 45-48).
Also available on the internet via WWW in PDF format.
Keywords: Romania. -- Ministerul Afacerilor Străine -- Management; Communication and technology -- Political aspects -- Romania; Romania -- Foreign relations administration